Dietary Fatty Acids Differentially Associate with Fasting Versus 2-Hour Glucose Homeostasis: Implications for The Management of Subtypes of Prediabetes - Guess, Nicola; Perreault, Leigh; Kerege, Anna; Strauss, Allison; Bergman, Bryan C. (PLOS ONE, 2016)
Over-nutrition has fuelled the global epidemic of type 2 diabetes, but the role of individual macronutrients to the diabetogenic process is not well delineated. We aimed to examine the impact of dietary fatty acid intake on fasting and 2-hour plasma glucose concentrations, as well as tissue-specific insulin action governing each. Normoglycemic controls (n = 15), athletes (n = 14), and obese (n = 23), as well as people with prediabetes (n = 10) and type 2 diabetes (n = 11), were queried about their habitual diet using a Food Frequency Questionnaire. All subjects were screened by an oral glucose tolerance test (OGTT) and studied using the hyperinsulinemic/euglycemic clamp with infusion of 6,62H2-glucose. Multiple regression was performed to examine relationships between dietary fat intake and 1) fasting plasma glucose, 2) % suppression of endogenous glucose production, 3) 2-hour post-OGTT plasma glucose, and 4) skeletal muscle insulin sensitivity (glucose rate of disappearance (Rd) and non-oxidative glucose disposal (NOGD)). The %kcal from saturated fat (SFA) was positively associated with fasting (β = 0.303, P = 0.018) and 2-hour plasma glucose (β = 0.415, P<0.001), and negatively related to % suppression of hepatic glucose production (β = -0.245, P = 0.049), clamp Rd (β = -0.256, P = 0.001) and NOGD (β = -0.257, P = 0.001). The %kcal from trans fat was also negatively related to clamp Rd (β = -0.209, P = 0.008) and NOGD (β = -0.210, P = 0.008). In contrast, the %kcal from polyunsaturated fat (PUFA) was negatively associated with 2-hour glucose levels (β = -0.383, P = 0.001), and positively related to Rd (β = 0.253, P = 0.007) and NOGD (β = 0.246, P = 0.008). Dietary advice to prevent diabetes should consider the underlying pathophysiology of the prediabetic state.